Resource Allocation in Cloud Computing: A Review - Mongia, Vikas; Kumar, Deepak (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing has quickly appeared as a outstanding standard for contributing IT infrastructure, resources and services on a pay-per-use basis from the last few years. Cloud computing is a promising technology and number of researches has been proposed for solving the issues faced by the cloud. There are number of challenges that a cloud is facing, from which, the main challenge is the resource allocation technique. Cloud permits the provisioning of resource on-demand. This procedure of allocating and re-allocating of resources is the way to accommodate the impulsive demands with an improvement of return on investment by means of infrastructure with the support of cloud. Resource allocation is the method in which the resources are allocated to each cloud user by the providers of cloud services. The varied factors like response time, cost, and dynamic allocation need to be acknowledged while choosing a technique of resource allocation. Though, in spite of the recent growth in cloud computing market, number of problems in the resource allocation remains unaddressed. This source course has introduced the significant concepts and the mechanisms of cloud computing and deliberates some research question on the topic while emphasizing on challenges and state-of-art solutions in the resource allocation. The article will expectantly inspire the future researchers to come up with the optimal and smarter resource allocation algorithms and structures to build up the paradigm of cloud computing